2012
DOI: 10.5194/acp-12-3241-2012
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mercury observations from Antarctica: seasonal variation and source and sink region calculations

Abstract: Abstract. Long term atmospheric mercury measurements in the Southern Hemisphere are scarce and in Antarctica completely absent. Recent studies have shown that the Antarctic continent plays an important role in the global mercury cycle. Therefore, long term measurements of gaseous elemental mercury (GEM) were initiated at the Norwegian Antarctic Research Station, Troll (TRS) in order to improve our understanding of atmospheric transport, transformation and removal processes of GEM. GEM measurements started in F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
93
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 38 publications
(52 reference statements)
10
93
2
Order By: Relevance
“…The station has been in operation since January/February 2007 and its current continuous measurements include mercury, CO, O 3 , particles, greenhouse gases, hydrocarbons, persistent organic compounds (POPs) and meteorological parameters (Hansen et al, 2009;Pfaffhuber et al, 2012). Mercury has been measured using the Tekran 2537B instrument since February 2007 with a 5 min sampling frequency.…”
Section: Methodsmentioning
confidence: 99%
“…The station has been in operation since January/February 2007 and its current continuous measurements include mercury, CO, O 3 , particles, greenhouse gases, hydrocarbons, persistent organic compounds (POPs) and meteorological parameters (Hansen et al, 2009;Pfaffhuber et al, 2012). Mercury has been measured using the Tekran 2537B instrument since February 2007 with a 5 min sampling frequency.…”
Section: Methodsmentioning
confidence: 99%
“…While the Arctic has been extensively monitored -with hundreds of publications focusing on AMDEs -measurements are sporadic in Antarctica. To the best of the author's knowledge, only 11 studies dealing with atmospheric mercury in Antarctica (and using modern instrument) have been published (Ebinghaus et al, 2002;Sprovieri et al, 2002;Temme et al, 2003;Brooks et al, 2008a, b;Dommergue et al, 2012;Pfaffhuber et al, 2012;Nerentorp Mastromonaco et al, 2016;Wang et al, 2016). The earliest studies showed the occurrence of AMDEs in coastal Antarctica after polar sunrise.…”
Section: Introductionmentioning
confidence: 99%
“…The maxima in July and August in the high resolution data look like a systematic feature whose origin has yet to be investigated. The seasonal variation at the Troll station (Pfaffhuber et al, 2012) is different with a maximum from April till July and a minimum in austral spring and summer (November -January). The difference is most likely due to mercury depletion events in Antarctica occurring during austral spring and summer (Steffen et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…All measurements were thus used in Fig. 1 Pfaffhuber et al (2012). In contrast to the absence of trends at both stations in the southern hemisphere, a decreasing trend of -0.049 ng m -3 yr -1 can be derived from the GEM monthly means at Mace Head since March 2007 until the end of 2011.…”
Section: Methodsmentioning
confidence: 99%